2001
DOI: 10.1007/s002280100282
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of CYP2D6 and CYP2C19 in East- and Southern African populations including psychiatric patients

Abstract: The genotype results predict a low prevalence of people with deficient CYP2D6 and CYP2C19 activity among linguistically (Bantu) related populations of East and Southern Africa. The high frequency of the low-activity CYP2D6*17 allele predicts that the Bantu people have a reduced capacity to metabolise drugs that are CYP2D6 substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
41
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 0 publications
10
41
0
1
Order By: Relevance
“…The consequences of polymorphic enzymes on drug metabolism in relation to efficacy and side effects has been the focus of numerous studies (Vandel et al, 1999;Dandara et al, 2001). For instance, individuals lacking the expression of a polymorphic drug-metabolizing enzyme (commonly referred to as "poor metabolizers" or PMs) will have higher drug exposure if those drugs are metabolized by those polymorphic enzymes, which could lead to exaggerated pharmacology or enhanced side effects relative to the intermediate metabolizer and extensive metabolizer (EM) subjects given the same dose (Mahgoub et al, 1977).…”
mentioning
confidence: 99%
“…The consequences of polymorphic enzymes on drug metabolism in relation to efficacy and side effects has been the focus of numerous studies (Vandel et al, 1999;Dandara et al, 2001). For instance, individuals lacking the expression of a polymorphic drug-metabolizing enzyme (commonly referred to as "poor metabolizers" or PMs) will have higher drug exposure if those drugs are metabolized by those polymorphic enzymes, which could lead to exaggerated pharmacology or enhanced side effects relative to the intermediate metabolizer and extensive metabolizer (EM) subjects given the same dose (Mahgoub et al, 1977).…”
mentioning
confidence: 99%
“…In linguistically related populations (Bantu) in Eastern and Southern Africa, a low prevalence of people with deficient CYP2D6 activity was found. However, the high frequency of the low-activity CYP2D6*17 allele predicts that the Bantu people have a reduced capacity to metabolize drugs that are CYP2D6 substrates [38]. Many studies of mutant alleles have demonstrated genetic heterogeneity in different black African populations [5].…”
Section: Dosage Predictionmentioning
confidence: 99%
“…This allele results in the production of an unstable enzyme, caused by a double amino acid substitution ( Table 1) [23]. The most commonly found allele in the African population is CYP2D6*17 [24]. It is also associated with an IM phenotype, resulting in reduced catalytic activity caused by a triple amino acid substitution ( Table 1) [23].…”
Section: Genetic Aspects Of Cyp2d6mentioning
confidence: 99%